Ligand recognition mechanism of thiamine pyrophosphate riboswitch aptamer - Uhm, H; Hohng, S (Korean Chemical Society, 2017)
Riboswitches regulate gene expression by coupling ligand binding to a structural transition of the riboswitch, but the coupling mechanism is still controversial. We addressed this issue by characterizing both the ligand-free state of the Escherichia coli thiamine pyrophosphate (TPP) riboswitch aptamer and its structural transition upon ligand binding using single-molecule fluorescence resonance energy transfer (FRET). Our results reveal that the apo-aptamer dynamically samples a partially closed form resembling the holo-aptamer, but TPP binding occurs in both the open and partially closed forms with the same efficiency. Mutation studies reveal that the preformation of the aptamer secondary structure is critical for TPP binding, and that tertiary interaction is established after TPP binding.